2022
DOI: 10.1097/md.0000000000029355
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempt using sodium nitrite ordered on the internet: Two case reports

Abstract: Rationale: Sodium nitrite is a potent oxidizing agent that impairs oxygen transport and delivery through methemoglobin formation. Clinical manifestations are known to induce methemoglobinemia, dysrhythmia, hypotension, and even death. While accidental intoxication of sodium nitrite by contaminated water and food has previously occurred, there has been a substantial upsurge in suicide intoxication in recent years. Patient concerns: We present case reports of 2 patients who attempted suicide by sodium nitrite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The 6 patients with intentional nitrite use all received methylene blue therapy. Increases in suicide attempts with sodium nitrite have been reported to be increasing, in part due to online information on its toxic effects coupled with availability of this compound through internet sources [37] , [53] , [54] , [55] . A set of twin infants had life-threatening methemoglobinemia from food contaminated with nitrates in a case investigated by public health authorities; both infants were treated with methylene blue [46] .…”
Section: Discussionmentioning
confidence: 99%
“…The 6 patients with intentional nitrite use all received methylene blue therapy. Increases in suicide attempts with sodium nitrite have been reported to be increasing, in part due to online information on its toxic effects coupled with availability of this compound through internet sources [37] , [53] , [54] , [55] . A set of twin infants had life-threatening methemoglobinemia from food contaminated with nitrates in a case investigated by public health authorities; both infants were treated with methylene blue [46] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, references from the literature found in search engines were searched for any omitted significant articles. A total of 128 individual papers [24,[29][30][31][32][34][35][36][37][39][40][41][42][43][44][45][46]48,49,53,56,57, describing in total 492 cases of intoxication were found. Analyzed cases were divided into groups according to the cause of intoxication, and how the causes of poisoning changed over the years was studied (Figure 2).…”
Section: Epidemiologymentioning
confidence: 99%
“…Toxics 2023, 11, 832 2 of 21 Canada [24], South Korea [34][35][36], Japan [37] Australia [38,39], Portugal [30], Spain [40], Poland [41], France [42], and Italy [43,44]. There are websites providing step-by-step instructions on how to commit suicide using sodium nitrite at home, further encouraging and describing this method as ideal due to its simplicity, quickness, and painlessness [45,46]. The origins of promoting the use of sodium nitrite as a method for suicide can be traced back to The Peaceful Pill Handbook, which recommends this method as simple, effective, peaceful, and painless [47].…”
Section: Introductionmentioning
confidence: 99%
“…9 Case reports from the US, Japan, and Korea have also confirmed that sodium nitrite is being ingested as a means of suicide. [19][20][21][22][23][24][25] In 2022, researchers surveyed this literature for cases of sodium nitrite ingestion. 11 Their review identified 132 cases, 53 of which were for suicidal purposes.…”
Section: Statisticsmentioning
confidence: 99%